Continuous-wave and actively Q-switched resonantly dual-end-pumped Er : YAG ceramic laser emitting at 1.6 μm. (December 2015) - Dai, T.Y.; Deng, Y.; Ju, Y.L.; Yao, B.Q.; Duan, X.M.; Wang, Y.Z.
Abstract: We demonstrate a continuous-wave (cw) and actively -switched Er : YAG ceramic laser resonantly dual-end-pumped by a fibre-coupled laser diode. A maximum cw output power of at is obtained at an absorbed pump power of, corresponding to a slope efficiency of 19.2 %. In the -switched regime the maximum pulse energy of is reached at a pulse repetition rate of, pulse duration of and absorbed pump power of .